Thermal Acclimation of Photosynthetic Electron Transport Activity by Thylakoids of Saxifraga cernua - Mawson, Bruce T. (1989)
Thermal acclimation by Saxifraga cernua to low temperatures results in a change in the optimum temperature for gross photosynthetic activity and may directly involve the photosynthetic apparatus. In order to test this hypothesis photosynthetic electron transport activity of S. cernua thylakoids acclimated to growth temperatures of 20°C and 10°C was measured in vitro. Both populations exhibited optimum temperatures for whole chain and PSII electron transport activity at temperatures close to those at which the plants were grown. Chlorophyll a fluorescence transients from 10°C-acclimated leaves showed higher rates in the rise and subsequent quenching of variable fluorescence at low measuring temperatures; 20°C-acclimated leaves showed higher rates of fluorescence rise at higher measuring temperatures. At these higher temperatures, fluorescence quenching rates were similar in both populations. The kinetics of State 1-State 2 transitions in 20°C- and 10°C-acclimated leaf discs were measured as changes in the magnitude of the fluorescence emission maxima measured at 77K. Leaves acclimated at 10°C showed a larger F730/F695 ratio at low temperatures, while at higher temperatures, 20°C-acclimated leaves showed a higher F730/F695 ratio after the establishment of State 2. High incubation temperatures also resulted in a decrease in the F695/F685 ratio for 10°C-acclimated leaves, suggesting a reduction in the excitation transfer from the light-harvesting complex of photosystem II to photosystem II reaction centers. The relative amounts of chlorophyll-protein complexes and thylakoid polypeptides separated electro-phoretically were similar for both 20°C- and 10°C-acclimated leaves. Thus, photosynthetic acclimation to low temperatures by S. cernua is correlated with an increase in photosynthetic electron transport activity but does not appear to be accompanied by major structural changes or different relative amounts in thylakoid protein composition.